Rancang Bangun Aplikasi Laporan Keuangan Berbasis Web Pada Pt. Anugrah Putra Kharisma - Sulistiowati; Januar Wibowo; Reris Pratama Putra (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
Anugrah Putra Kharisma is a company that carries out the business of buying land, building houses to selling houses. To support this business, one of the activities at PT. Anugrah Putra Kharisma is managing the company's financial data by making financial reports in the form of income and expense reports. The problem is that so far the preparation of financial reports takes a long time because every transaction is recorded in the books by the Administration Section. Furthermore, the transaction data is entered and processed with the Microsoft Excel application. This causes the process of making financial statements takes a long time. Based on these problems, the solution offered in this study is to design a web-based financial statement application at PT Anugrah Putra Kharisma. This financial report application consists of managing daily financial reports, monthly financial reports, annual financial reports, and printing reports. By utilizing the application of financial statements can help companies to solve existing problems.